A case of primary disseminated rhinosporidiosis and dapsone-induced autoimmune hemolytic anemia: A therapeutic misadventure. (2021) - Ghosh, Ritwik; Mondal, Subhargha; Roy, Dipayan; Ray, Adrija; Mandal, Arpan; Benito-León, Julián
Abstract: Rhinosporidiosis, a chronic inflammatory disease, which is caused by the aquatic microorganism Rhinosporidium seeberi, is endemic in India and in many other regions of the tropics. It primarily infects mucocutaneous surfaces of nose, nasopharynx, and conjunctiva through transepithelial invasion. However, over the centuries, atypical involvement of other body parts, especially viscera, bone, subcutaneous layers, genitals, the tracheobronchial tree, and even the skull has been, though rarely, reported. This chronic granulomatous infection is notorious for its propensity for recurrence following autoinoculation and poor response to most of the anti-microbials except dapsone. Surgical excision followed by cauterization remains the treatment of choice when an operation is feasible. We herein report a case of an immunocompetent person with primary disseminated dermato-pulmonary rhinosporidiosis, which created significant diagnostic dilemma at the beginning, got complicated due to dapsone-induced direct anti-globulin test-positive autoimmune hemolytic anemia, and finally responded to prolonged multidrug therapy with liposomal amphotericin B, ketoconazole and cycloserine. This report establishes the importance of tissue diagnosis in rhinosporidiosis and even, in resource-poor set-ups, a simple histopathological diagnosis can promote an early and affordable accurate diagnosis, and subsequently, a proper therapeutic intervention.